Math, asked by sivabasaksh7rishr, 1 year ago

Split the middle term 6x^2+7 root 2x+4

Answers

Answered by mysticd
107

Answer:

6x²+7√2x+4

= (3x+2√2)(2x+√2)

Or

= √2(√2x+1)(3x+2√2)

Explanation:

Given quadratic expression:

6x²+72x+4

Splitting the middle term, we get

= 6x²+42x+32x+4

= 6x²+2(22)x+32x+(2)(22)

= 2x(3x+22)+2(3x+22)

= (3x+22)(2x+√2)

Or

= (3x+2√2)[2(2x+1)]

= 2(2x+1)(3x+22)

Therefore,

6x²+7√2x+4

= (3x+22)(2x+2)

Or

= 2(2x+1)(3x+22)

Answered by mindfulmaisel
58

We split the ‘middle term’ of the 6 x^{2}+7 \sqrt{2 x}+4, we get the value \bold{(3 x+2 \sqrt{2})(2 x+\sqrt{2})}

To find:

Split the ‘middle term’ of the given equation 6 x^{2}+7 \sqrt{2 x}+4

Solution:

6 x^{2}+7 \sqrt{2 x}+4

=6 x^{2}+4 \sqrt{2 x}+3 \sqrt{2 x}+4

=2 \times 3 \times x^{2}+2 \times 2 \sqrt{2 x}+3 \sqrt{2} x+2(2)

=2 x(3 x+2 \sqrt{2})+\sqrt{2}(3 x+2 \sqrt{2})

=(3 x+2 \sqrt{2})(2 x+\sqrt{2})

A polynomial is an expression consisting of ‘variables’ and ‘coefficients’ that involves the arithmetic operations like ‘addition’, ‘subtraction’, and ‘non-negative integer exponents’ of variables.

Similar questions